Impairment in the behavioral control of body sway, gaze shift, and mental workload in Parkinson’s disease - Yann-Romain Kechabia; Luc Defebvre; Arnaud Delval; Cédrick T. Bonnet (Scientific Reports)
Abstract We tested Parkinson’s disease (PD)-related impairments in the relationship between gaze shifts, body sway and mental workload while performing visual tasks in the standing position. Nineteen on-drug PD patients (Hoehn and Yahr I-II; MDS-UPDRS score part III: 23.37 ± 2.79) and twenty age-matched controls explored large images (visual angle: 100°) and performed a search task (location of targets within images) as well as a free-viewing (control) task. To collect kinematic data, all participants wore body markers (lower back, upper back and head) and an eye tracker. PD patients showed a higher amplitude in gaze shifts and body sway than age-matched controls. The adaptation of gaze shift and body sway velocity from free-viewing to searching was smaller in PD patients. The mental workload (NASA-TLX score) was a significant covariate in all participants. Furthermore, the MDS-UPDRS score was a significant covariate in the shared variance between body (lower back, upper back and head) and eye movement, thus showing a relation between this clinical variable and impairment at the behavioral level. Our results indicate impaired behavioral synergic, i.e. complementary, control between vision, posture and mental workload in PD patients. With a view to restoring synergic functional control, rehabilitation programs should train the three systems together simultaneously.